2021
DOI: 10.33899/ijvs.2020.126832.1394
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Neospora caninum infections in cattle in Kirkuk province

Abstract: Neospora caninum was identified as a coccidian parasite as in 1988, before that date it was misclassified as Toxoplasma gondii based on structural similarities. The aim of this study was to determine the seroprevalence of N. caninum in cattle in Kirkuk Province. A total of 185 cattle serum samples were collected randomly. Data about ages, gender and abortion history of females were recorded. Serum samples were examined by using ELISA as a screening test for the detection of anti-N. caninum IgG antibodies of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…This could suggest the vertical transmission of the parasite and its involvement in small ruminants and equines abortion. Consistently, neosporosis was previously reported in range of 17.4% to 28.6% in aborted and healthy bovines according to the diagnostic approaches with ELISA and PCR assays in Iraq (AL-Badrani 2012, Nooruldeen et al 2021. In Wasit province (Iraq) it was showed that the prevalence rate of N. caninum was 13.7% in aborted ovine foetuses (Al-Shaeli et al 2020) and 18.9% in aborted caprine foetuses (Faraj and Ghattof 2018).…”
Section: Discussionsupporting
confidence: 60%
“…This could suggest the vertical transmission of the parasite and its involvement in small ruminants and equines abortion. Consistently, neosporosis was previously reported in range of 17.4% to 28.6% in aborted and healthy bovines according to the diagnostic approaches with ELISA and PCR assays in Iraq (AL-Badrani 2012, Nooruldeen et al 2021. In Wasit province (Iraq) it was showed that the prevalence rate of N. caninum was 13.7% in aborted ovine foetuses (Al-Shaeli et al 2020) and 18.9% in aborted caprine foetuses (Faraj and Ghattof 2018).…”
Section: Discussionsupporting
confidence: 60%
“…The prevalence was calculated using descriptive statistics on Excel program 2010, and the Relative Risk was analyzed for epidemiological factors using the statistical program Epi-Info V.7.2, and the Significant P<0.05 differences between affected groups and control group, (8).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic commercial kit indirect ELISA assay ID.vet, 310, rue Louis Pasteur-Grabel -France, has been utilized to diagnose Hypoderma spp. for IgG antibodies in bovine serum which also has been applied by (11,12). Microplates coated with hypodermines A, B and C from Hypoderma spp.…”
Section: Indirect Elisa Technique (Ielisa)mentioning
confidence: 99%